Rising Trends of Overweight and Obesity among Women in India - Vartika Saxena (Indian Association of Preventive and Social Medicine, 2022)
Overweight and obesity have reached epidemic proportions globally, with a world- wide prevalence of around 39%. It is the fifth leading cause of death, resulting in about 2.8 million deaths of adults globally every year. Diabetes (44%), Ischemic heart disease (23%) and certain cancer(7-14%) burdens are attributable to overweight or obesity. The problem is not only restricted to developed countries but poses a new challenge for developing countries, [3] calling for immediate attention. In developed countries, food patterns like energy-dense food consumption and sedentary lifestyles may contribute to this increasing burden of obesity. While in developing countries like India, there is a transition from traditional food patterns to more westernized food which includes highly-saturated fats, sugar, and refined food. Apart from this, reduced levels of physical activity, better transport facilities, better healthcare, and increased stress, particularly in the rapidly-growing urban populations, are all critical factors leading to an increased burden of obesity in India. According to the National Nutritional Monitoring Bureau (NNMB) report (2012), the prevalence of overweight/obesity was significantly higher in those with high consumption levels of milk and milk products, fats and oils, sugar, and salt. India has more than 30 million obese people, which is increasing alarmingly. The problem is more acute among women than men. In India, the proportion of overweight or obese women is 24%, one percent higher than that of men (23%).